Studies on Brown Midrib 6 and 12 Genes Introgression in Two Nigerien and One Malian Sorghum Varieties: A Practical Guide to Young Scientists with Limited Molecular Facility - Diakité, Ousmane Seyni; Aissata, Mamadou; Aliou, Sissoko; Sekouba, Sanogo; Kouressy, Mamoutou; Michel, Vaksmann; Dzidzienyo, Daniel K.; Eric, Danquah; Pangirayi, Tongoona; Traoré, Karim; Teme, Niaba (Current Approaches in Science and Technology Research Vol. 12, 2021)
Introgression of bmr genes from less adapted donor parent to well adapted high yielding biomass varieties with poor nutritional value is very important for sustainable cattle feeding during pasture scare time in the Sahel. The main objective of this work was to introgress bmr6 and bmr12 genes in Nigerien and Malian sorghum varieties background for dual purpose grain and biomass potential. The plant material was composed of two improved sorghum varieties (Sepon82 and Kalla Kéné) and El mota a farmer preferred variety as recurrent parents. bmr donor parents were redlan bmr6, Tx630 bmr12 and Wheatland bmr12. The hand emasculation technique was used to introgress bmr genes in recurrent parents to produce F3 and BC1F3 populations at Sotuba research Station in Mali from January 2016 to June 2017. This technique is still very useful in genes introgression for sorghum segregating populations development. Anthocyanin pigment and heterosis effects were key phenotypic traits to identify F1 and BC1F1 plants during the population development. Anthocyanin allowed the identification of F1 plants in a cross involving anthocyanin (purple plant) and tan plants, while for both tan plants cross, heterosis effect was major key to discriminate F1 from parental lines and bmr segregation in F2 to ascertain successful crosses. The x2 test was used to analyze bmr segregation ration. Segregation ratios of bmr plants in F2 and BC1F2 showed a good fit of a single recessive gene (3:1). bmr 6 and 12 genes were successfully transferred to three recurrent parents varieties which are at F4 and BC1F3 generation for grain and biomass yields potential tests in Niger during the 2017 cropping season.